2016
DOI: 10.1515/helmin-2015-0071
|View full text |Cite
|
Sign up to set email alerts
|

Nematodes from Achatina fulica Bowdich, 1822 (Mollusca: Gastropoda) in Argentina

Abstract: SummaryThe aim of this study is to describe the nematode cysts and larvae found in Achatina fulica, the giant African snail, in the northeast of Argentina. A total of 373 snails were collected from the cities of Puerto Iguazú and Corrientes. Cysts (N= 2958) containing nematodes identifi ed as L3 Strongyluris sp. were found in the mantle cavity of 87 snails from Puerto Iguazú City (Prevalence 23 %; Mean Intensity= 34; Mean Abundance= 8). The shell size correlated with prevalence, mean intensity and mean abundan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
(11 reference statements)
1
7
0
1
Order By: Relevance
“…(1) agriculture, destructing crops; (2) human health, acting as an intermediate host of several parasites, e.g. nematodes Angiostrongylus costaricensis (Morera and Cespedes, 1971), A. cantonensis (Chen, 1935), and Aelurostrongylus abstrusus (Raillet, 1898); (3) native fauna, via inter-specific competition (Thiengo et al 2007;Thiengo and Fernández 2016;Valente et al 2016).…”
Section: Relationship Between Nnms Richness and Urbanized Areas And Tmentioning
confidence: 99%
“…(1) agriculture, destructing crops; (2) human health, acting as an intermediate host of several parasites, e.g. nematodes Angiostrongylus costaricensis (Morera and Cespedes, 1971), A. cantonensis (Chen, 1935), and Aelurostrongylus abstrusus (Raillet, 1898); (3) native fauna, via inter-specific competition (Thiengo et al 2007;Thiengo and Fernández 2016;Valente et al 2016).…”
Section: Relationship Between Nnms Richness and Urbanized Areas And Tmentioning
confidence: 99%
“…Then, we can consider that the infection of Achatina fulica by Strongyluris spp. larvae could be explained by the role of the snail as an intermediate host, as observed by Valente et al (2016). This hypothesis can be accepted, as Fischer et al (2010) mentions that the habitat and habits of A. fulica facilitate the parasitism in this species.…”
Section: Discussionmentioning
confidence: 86%
“…2D). These morphological characteristics were also described by Thiengo (1995), Franco-Acuña et al (2009), and Valente et al (2016 to L3 larvae identified as Strongyluris sp. (family Heterakidae).…”
Section: Nematode Identificationmentioning
confidence: 77%